2002
DOI: 10.1007/bf02930656
|View full text |Cite
|
Sign up to set email alerts
|

A unified characterization of reproducing systems generated by a finite family, II

Abstract: By a "reproducing" method for H = L 2 (R n) we mean the use of two countable families {e α : α ∈ A}, {f α : α ∈ A}, in H, so that the first "analyzes" a function h ∈ H by forming the inner products {< h, e α >: α ∈ A}, and the second "reconstructs" h from this information: h = α∈A < h, e α > f α. A variety of such systems have been used successfully in both pure and applied mathematics. They have the following feature in common: they are generated by a single or a finite collection of functions by applying to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(189 citation statements)
references
References 26 publications
7
182
0
Order By: Relevance
“…This result recovers Theorem 5.9 in [13] and, as shown in that paper, it generalizes and contains all classical characterization results about affine systems, including those in [4,6,11,23]. We refer to the same paper for more details about the motivation and history of these and similar characterization equations for the affine systems in L 2 (R n ).…”
Section: Affine Systemssupporting
confidence: 82%
See 2 more Smart Citations
“…This result recovers Theorem 5.9 in [13] and, as shown in that paper, it generalizes and contains all classical characterization results about affine systems, including those in [4,6,11,23]. We refer to the same paper for more details about the motivation and history of these and similar characterization equations for the affine systems in L 2 (R n ).…”
Section: Affine Systemssupporting
confidence: 82%
“…Several papers have been devoted to the formulation and study of these characterizations, and they play a major role in the construction and study of Gabor and affine systems (for example, [3,4,6,10,11,14,17,19,[21][22][23]). The approach that we develop in this paper adapts some ideas from [13,19], where one of the present authors has developed a unified approach to Gabor systems and affine systems in L 2 (R n ).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of these various definitions is made is [137]. In [139] it is shown that the local integrability condition of [114] is equivalent to finite affine Beurling density (assuming some mild regularity on the wavelet ψ). The role of density conditions in wave packet systems (which combine translations, modulations, and dilations together) is explored in [47].…”
Section: Waveletsmentioning
confidence: 99%
“…Using the distributional version Theorem 1.2 makes the derivation of these important results conceptually simple and in addition avoids the technicalities connected with the L 2 -boundedness. For a unified treatment of reproducing systems, see [19,28,30].…”
Section: Remark 43 Recall That G Is Called a Bessel Sequence Ifmentioning
confidence: 99%